Clinical and angiographic features of SCAD type 4. (15th April 2023) - Mori, Ricardo; Macaya, Fernando; Giacobbe, Federico; Salinas, Pablo; Rolfo, Cristina; Porto, Italo; Gonzalo, Nieves; Varbella, Ferdinando; Cerrato, Enrico; Escaned, Javier
Abstract: Introduction: The angiographic type 4 in SCAD is described as a total occlusion of the coronary artery and its management may differ according to its clinical presentation. We previously have observed that these patients present a low incidence of adverse events. Our objective was to describe clinical and angiographic characteristics of this condition, according to its initial management in the DISCO registry. Methods: We conducted an observational study of consecutive SCAD patients from 26 centres of Italy and Spain (DISCO registry). Angiotype 4 SCAD cases were selected and classified according to the initial treatment chosen: conservative management vs. percutaneous coronary intervention (PCI). Clinical and angiographic characteristics were compared. Results: We recruited 81 (mean age 52.6 ± 11 years) patients with SCAD angiotype 4 out of 302 patients of the DISCO registry. Thirty-eight (46.9%) patients received conservative management and 43 (53.1%) received PCI. Nearly all patients undergoing PCI had ST-segment elevation (93% vs 47.4%, p  < 0.0001), the left anterior descending artery (LAD) was more commonly involved (67.4% vs. 42.1%, p  = 0.006), and they had more frequent proximal segment involvement (25.6% vs 2.7%, p  = 0.004) and longer lesions (46.5 ± 23.2 mm vs 26.4 ± 18.8 mm, p  = 0.017). On the other hand, non-ST-segment elevation myocardial infarction (52.6% vs 2.3%, p  = 0.001) and isolated involvement of secondary branches (55.3 vs 4.7, p  < 0.0001) were more common in the conservative management group. Conclusions: Patients with SCAD angiotype 4 who underwent PCI had a higher frequency of STEMI and involvement of proximal and longer coronary segments, particularly affecting the left anterior descending artery. NSTEMI and isolated involvement of secondary branches were more frequently found in those managed conservatively. Highlights: Spontaneous coronary artery dissection (SCAD) is recognized as an important cause of acute coronary syndrome (ACS) leading to myocardial infarction. Angiotype 4 SCAD is described as a total occlusion of the coronary artery and its management may differ according to its clinical presentation. Angiotype 4 SCAD presented a low incidence of adverse clinical events during admission and in long-term follow-up. SCAD patients with an angiotype 4 are more propense to receive revascularisation when they present with STEMI, when the vessel is the LAD and when long and proximal segments are involved.